TOWARDS A TRANS-DISCIPLINARY PERSPECTIVE FOR POLICE SCIENCE - Bakharuddin Muhammad Syah; Rendy Ananta Prasetya (Jurnal Scientia, 2023)
The study was intended to determine the development of police science through a transdisciplinary approach. Therefore in this study, the researcher used the literature review-based method to understand the object of the study. The instrument of the study was using literature approach. This writing shows that in developing the police as a form of science and discipline, police science must integrate with other sciences and disciplines. Police science can use perspectives, paradigms and even methodologies developed by other sciences to develop themselves to obtain a more comprehensive and detailed understanding, thus further assisting in the analysis process by police science. The process of developing police science as a science that integrates with other sciences can be seen from the existence of police anthropology. Police anthropology is a sub-discipline resulting from the transdisciplinary relationship between police science and anthropology. Police science in police anthropology began to focus on "police" or "police" (its institutional form) tied to social practices, where "policemen" create, maintain, and invest in existing socialities in different ways. Understanding "police" is not limited to security apparatus, law enforcement or formal community institutions. However, furthermore, there is an aspect of breadth in the concept of "police" which cannot be separated from society’s social world. The development of police understanding tied to the existing social structure enables police science to explore local-national and global problems. This is considering that most people already have cross-border connectivity due to information and digital technology development.